Surgical Exposure of Impacted Upper Right central Incisor and Its Proper Alignment in the Dental Arch (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Reported case is of a 9-year-old-girl with unerupted malposed upper right central incisor, which was treated by sequential surgical exposure and fixed orthodontic treatment. The tooth was aligned in the dental arch with accepted aesthetic and functional satisfaction of the patient. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15986 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 16-17